STRIATAL ACTIVITY NEUROPHARMACOLOGICL MODULATIONIN CONDITIONS OF CHRONIC SEIZURE ACTIVITY - Vastyanov, R.S.; Topal, M.M.; Stoyanov, A.N.; Broshkov, M.M.; Galuzinskaya, M.I.; Levkovskaya, V.Yu.; Shpota, Ye.Ye. (World of Medicine and Biology, 2019)
The aim of the work was to investigate the swimming behavior throughout the interseizure period of chronic seizure syndrome two models – picrotoxin (PTX)-induced kindling and pilocarpine (PL)-induced convulsions in conditions of intrastriatal choline-, dopamine- and GABA-ergic neurotransmission modulation. The experimental trials on rats revealed the enhancement of striatal choline- and dopamine-ergic neurotransmission together with GABA-ergic mechanisms failure was established in conditions of PTX- and PL-induced chronic seizure activity. Striatal choline- and dopamine-ergic neurotransmission activation together with GABA-ergic mechanisms inhibition were registered during the middle interseizure period in kindled rats characterized by the expressed changes of swimming behavior in the form of variability reduction and animals’ escape from the pool failure. Swimming behavior similar changes were registered in rats with PL-induced seizures in case of striatal choline- and dopamine-ergic neurotransmission inhibition and GABA-ergic mechanisms activation. Rats swimming behavior at the end interseizure period characterized by their immobility and improvement of ability of switching on active-adaptive behavior formation in case of striatal choline- and dopamine-ergic neurotransmission activation together with GABA-ergic mechanisms inhibition in PTX-kindled rats. The swimming behaviour opposite mechanisms were evident in case of PL-induced seizures. Thus, striatal hiperactivation determines PTX- and PL-induced chronic seizure activity development.
Keywords: pilocarpine; picrotoxin; interseizure period; striatum; intrastriatal neurotransmission; striatal hiperactivation